Berliner Aufzeichnungen. - Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1985)
Bunne, Egon ; Frenzel, Hanna ; Gramming, Walter ; Oehme, Anke ; Jahn, Ebba ; Johannsen, Kirsten ; El Malki, Ellen ; Morris, Michael ; Trasov, Vincent ; Wolkenstein, Rolf S. ; Fischer, Ricarda ; Peeck, Joachim ; Yo, Yana
Berliner Aufzeichnungen / Berlin Notes, Walter Phillips Gallery, The Banff Centre for the Arts, Banff, June 6-30, 1985
boek